(untitled) (International Journal of Engineering and Computer Science, 2017)
A sensor is a device which is able to convert any objective quantity to be measured into a signal which is interpreted, displayed, stored or used to control some other data. The signal formed by the sensor is equal to the quantity to be measured. Sensors are used to calculate a particular characteristic of any object or device.[1] This paper provides the overview about What is sensors, different fields where sensors are used, how sensors are used in day to day life, its advantages and disadvantages and types of sensors. Paper also gives idea about how sensors plays an important role in cyber security.